The Role of the Nurse in Renal Care - A.M. de Kleijn (AOSIS, 1978)
Recently we have been made aware by our nursing leaders that the nurse must extend her role. Professor Eleanor Lambertson, Dean of the School of Nursing. Cornell University, New York, has said and I quote: "It is my premise that until and unless nurses willingly face the issues associated with the extension of their scope of practice, nurses will become obsolete in terms of today's and tomorrow's need for health care services."